2019 IEEE International Symposium on Olfaction and Electronic Nose (ISOEN) 2019
DOI: 10.1109/isoen.2019.8823147
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Plume Tracking as a Strategy for Gas Source Localization in Turbulent Wind Flows

Abstract: Gas source localization is likely the most direct application of a mobile robot endowed with gas sensing capabilities. Multiple algorithms have been proposed to locate the gas source within a known environment, ranging from bio-inspired to probabilistic ones. However, their application to real-world conditions still remains a major issue due to the great difficulties those scenarios bring, among others, the common presence of obstacles which hamper the movement of the robot and notably increase the complexity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It refers to the use of mobile robots in combination with a sensing technology to perceive gas release in the environment [30]. Recent advancements in the design and development of gas sensors and drone technology as well as the adaptation of Artificial Intelligence and Machine Learning techniques for processing signals from sensors and robotics control have revealed RO as interesting research field in many practical applications [31,32].…”
Section: Robot Olfactory Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…It refers to the use of mobile robots in combination with a sensing technology to perceive gas release in the environment [30]. Recent advancements in the design and development of gas sensors and drone technology as well as the adaptation of Artificial Intelligence and Machine Learning techniques for processing signals from sensors and robotics control have revealed RO as interesting research field in many practical applications [31,32].…”
Section: Robot Olfactory Problemmentioning
confidence: 99%
“…A general and powerful extension in this research field suggested in different studies as a potential future development, is the adaptation of methodologies for the third spatial dimension and for augmenting the solution to a multirobot collaboration scheme. These improvements in many cases may help to reduce the time needed to cover a large area and improve at the same time the quality of the sampled data when a low-cost multisensory system is used [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Drones In the Gsl Applicationmentioning
confidence: 99%